Morphea: Evidence-based recommendations for treatment - Fett, Nicole (Indian journal of dermatology, venereology, and leprology, 2012)
Morphea is a rare fibrosing disorder of the skin. Evidence-based treatment strategies in morphea are lacking. This review summarizes the available data on morphea treatment and provides therapeutic strategies based on morphea subtypes. The Cochrane Library, Medline and Embase from inception until May of 2011 were searched using the key words "morphea" and "morphea treatment." Reference lists of the resultant articles, as well as relevant reviews, were also searched. This review focuses on randomized controlled trials, prospective interventional trials without controls and retrospective reviews with greater than five subjects.